Peran Pokdarwis dalam Pertumbuhan Desa Wisata Pujon Kidul - ; Sendy Fransiscus Tantono Putro (Syntax Idea)
Tourism village as a tourism destination is a proven way out for improving society’s welfare as well as a sustainable tourism destination. This paper aims for demonstrating initial effort in a community in order to build tourism village, in accordance to the sustainable tourism development. This literature study shows that tourism awareness group called Pokdarwis has succeeded in building strong relationship in community to realize the vision of improving welfare of village community. This success is shown from the establishment of nine business units (BUMdes) and the increasing welfare of community with the opening of new positions in tourism sectors.